Identification of individual tetra- and pentacyclic naphthenic acids in oil sands process water by comprehensive two-dimensional gas chromatography/mass spectrometry - Rowland, S.; West, C.; Scarlett, Alan; Jones, D.; Frank, R. (2011)
The oils sands industry of Canada produces large volumes of process water (OSPW) which is stored in large lagoons. The OSPW contains complex mixtures of somewhat toxic, water-soluble, acid-extractable organic matter sometimes called 'naphthenic acids' (NA). Concerns have been raised over the possible environmental impacts of leakage of OSPW and a need has therefore arisen for better characterisation of the NA. Recently, we reported the first identification of numerous individual tricyclic NA in OSPW by comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (GCxGC/ToF-MS) of the methyl esters. The acids were diamondoid adamantane acids, resulting, it was proposed, from biotransformation of the corresponding alkyladamantane hydrocarbons, which is a known process. Biotransformation of higher alkylated diamondoid hydrocarbons was, until now, unknown but here we describe the identification of numerous pentacyclic NA as diamantane and alkyldiamantane acids, using the same methods. Further, we suggest tentative structures for some of the tetracyclic acids formed, we propose, by ring-opening of alkyldiamantanes. We suggest that this is further evidence that some of the acid-extractable organic matter in the OSPW originates from extensive biodegradation of the oil, whether in-reservoir or environmental, although other oxidative routes (e.g. processing) may also be possible. The results may be important for helping to better focus reclamation and remediation strategies for NA and for facilitating the identification of the sources of NA in contaminated environmental samples. © 2011 John Wiley & Sons, Ltd.